Pemanfaatan Ubi Jalar Putih Sebagai Media Alternatif Untuk Pertumbuhan Bibit F0 Jamur Tiram dan Jamur Merang - Hartati, Sri, Dra. Suparti, M.Si (2017)
White sweet potato is one of type varieties of sweet potato containing carbohydrate as much as 27.9 g, and vitamin C 22 mg, so it can be provided the nutrition for the growth of mycelium mushroom. This study aims to know the growth of mycelium and thickness F0 oyster mushroom and straw mushroom. The research used descriptive qualitative by using experiment research design. The reseach design used Completely Randomized Design (RAL) factorial pattern consist of two factors: F1: the types of media such as extract media, porridge and white sweet potato flour, and F2: the type of mushroom such as oyster mushroom and straw mushroom. Technique of analysis data used descriptive qualitative. The results of the research shown that the fastest growth diameter of mycelium in porridge medium, oyster mushroom (M2J2) which is 5.75 cm, and flour medium (M3J2) which is 9 cm and the slowest growth in extract media, oyster mushroom (M1J1) that is 1.95 cm.